2016
DOI: 10.3390/brainsci6010006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypoxia and Inflammation on Synaptic Signaling in the CNS

Abstract: Normal brain function is highly dependent on oxygen and nutrient supply and when the demand for oxygen exceeds its supply, hypoxia is induced. Acute episodes of hypoxia may cause a depression in synaptic activity in many brain regions, whilst prolonged exposure to hypoxia leads to neuronal cell loss and death. Acute inadequate oxygen supply may cause anaerobic metabolism and increased respiration in an attempt to increase oxygen intake whilst chronic hypoxia may give rise to angiogenesis and erythropoiesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 104 publications
2
87
0
5
Order By: Relevance
“…; Mukandala et al . ). This response is adaptive at a local level, as it reduces metabolic demands, enhancing the capacity of brain tissue to survive periods of limited O 2 supply, but hypoxic depression of respiratory network activity is maladaptive; i.e.…”
Section: Attenuation Of the Hypoxic Ventilatory Response By Disruptiomentioning
confidence: 97%
“…; Mukandala et al . ). This response is adaptive at a local level, as it reduces metabolic demands, enhancing the capacity of brain tissue to survive periods of limited O 2 supply, but hypoxic depression of respiratory network activity is maladaptive; i.e.…”
Section: Attenuation Of the Hypoxic Ventilatory Response By Disruptiomentioning
confidence: 97%
“…19 However, physiologic concentrations of NaHS have been shown to attenuate secretion of proinflammatory cytokines. 20,21 Whether the effect of NaHS on cytokine production is a dose dependent function is unclear.…”
Section: Accepted Articlementioning
confidence: 99%
“…It has been reported that under hypoxic insult, the activity of HIF-1 and expression of its associated downstream genes, such as vascular endothelial growth factor (VEGF) and erythropoietin (EPO) are altered in a range of neurodegenerative diseases (NDDs) including Alzheimer's disease (AD), Parkinson's disease (PD) and Amyotrophic lateral sclerosis (ALS) [4]. It has also been reported that hypoxia causes reduced synaptic transmission associated with neuronal death by causing neuronal dysfunction [5]. Thus, elucidation of pathophysiological mechanisms caused due to hypoxic insults on the cerebral nervous system (CNS); their therapeutic regulation awaits much importance.…”
Section: Introductionmentioning
confidence: 99%